The Use of the Fiberglass at the Reinforced Concrete Elements - Răzvan Giuşcă; Vladimir Corobceanu (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2005)
The main constituent of the reinforced fiberglass concrete are: the glass fibers, the binder, the sand and the water. In order to change certain characteristics there can be used different types of additives of fillers. The fiberglass is used in the shape of beams and cords having the lengths comprised between 12 and 15 mm; the cutting is realized with different devices, which are designed, built and used by variant firms. The reinforced fiberglass concretes use the following binders: hydraulic binders - based on Portland cement, like the normal Portland cement, the Portland cement with additions, the fast - hardening cement (in Romania the RIM), the white and coloured cements; the alumina cements, non-hydraulic binders - the burnt plaster, the magnesite cement, clay.